Wireless multimedia communications : convergence, DSP, QoS, and security /: convergence, DSP, QoS, and security. (2018) - Rao, K. Ramamohan (Kamisetty Ramamohan); Bojkovic, Z. S; Milovanovic, Dragorad A
No abstract available